Penerapan Teknik Akrostik Untuk Meningkatkan Keterampilan Menulis Puisi Siswa Madrasah Ibtidaiyah - Ina Diana; Nasihudin Nasihudin (Jurusan Pendidikan Guru Madrasah Ibtidaiyah, 2018)
The purpose of this study was to determine students' poetry writing skills before the application of acrostic techniques, the process of applying acrostic techniques in each cycles, and the increase produced after applying the acrostic technique. The research method used is Classroom Action Research (CAR), consisting of planning, implementing, observing, and reflecting. Based on data analysis, it was concluded that 1) the students' poetry writing skills before applying the acrostic technique obtained an average score of 46.87. 2) The application of acrostic techniques goes well according to the stages. The activity of teachers and students has increased dramatically, in the first cycle the teacher's activity gained a percentage of 64.15%, in the second cycle teacher activity increased to 89.1%. Student learning activities in the first cycle reached 61.65%, in cycle II it increased by 87.5%. 3) Students' poetry writing skills after applying acrostic techniques have increased. In the first cycle, the average score of students was 69.45, and the percentage of learning completeness was 51.75%. In cycle II the average value of students skill increased sharply to 89.37, and the percentage was 91%. Thus, the CAR carried out has been completed with the expected goal of improving poetry writing skills in Indonesian Language Subjects.